Modeling Environmental DNA Transport in the Coastal Ocean Using Lagrangian Particle Tracking - Andruszkiewicz, Elizabeth A.; Koseff, Jeffrey R.; Fringer, Oliver B.; Ouellette, Nicholas T.; Lowe, Anna B.; Edwards, Christopher A.; Boehm, Alexandria B. (Frontiers in Marine Science, 2019)
A number of studies have illustrated the utility of environmental DNA (eDNA) for detecting marine vertebrates. However, little is known about the fate and transport of eDNA in the ocean, thus limiting the ability to interpret eDNA measurements. In the present study, we explore how fate and transport processes affect oceanic eDNA in Monterey Bay, California, USA (MB). Regional ocean modeling predictions of advection and mixing are used for an approximately 10,000 km2 area in and around MB to simulate the transport of eDNA. These predictions along with realistic settling rates and first-order decay rate constants are applied as inputs into a particle tracking model to investigate the displacement and spread of eDNA from its release location. We found that eDNA can be transported on the order of tens of kilometers in a few days and that horizontal advection, decay, and settling have greater impacts on the displacement of eDNA in the ocean than mixing. The eDNA particle tracking model was applied to identify possible origin locations of eDNA measured in MB using a quantitative PCR assay for Northern anchovy (Engraulis mordax). We found that eDNA likely originated from within 40 km and south of the sampling site if it had been shed approximately 4 days prior to sampling.